Comparison of Cryptococcus gattii/neoformans Species Complex to Related Genera (Papiliotrema and Naganishia) Reveal Variances in Virulence Associated Factors and Antifungal Susceptibility - Oliveira, Lana Sarita de Souza; Pinto, Luciana Magalhães; de Medeiros, Mariana Araújo Paulo; Toffaletti, Dena L.; Tenor, Jennifer L.; Barros, Tânia Fraga; Neves, Rejane Pereira; Neto, Reginaldo Gonçalves de Lima; Milan, Eveline Pipolo; Padovan, Ana Carolina Barbosa; Rocha, Walicyranison Plinio da Silva; Perfect, John R.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptococcosis is an infectious disease of worldwide distribution, caused by encapsulated yeasts belonging to the phylum Basidiomycota. The genus Cryptococcus includes several species distributed around the world. The C. gattii/neoformans species complex is largely responsible for most cases of cryptococcosis. However, clinical series have been published of infections caused by Papiliotrema (Cryptococcus) laurentii and Naganishia albida (Cryptococcus albidus), among other related genera. Here, we examined the pathogenic potential and antifungal susceptibility of C. gattii/neoformans species complex (clades I and II) and related genera (Papiliotrema and Naganishia) isolated from environmental and clinical samples. P. laurentii (clade III), N. liquefasciens/N. albidosimilis (clade IV); and N. adeliensis/N. albida (clade V) strains produced higher levels of phospholipase and hemolysins, whereas the C. gattii/ neoformans species complex strains (clades I and II) had markedly thicker capsules, produced more biofilm biomass and melanin, which are known virulence attributes. Interestingly, 40% of C. neoformans strains (clade II) had MICs above the ECV established for this species to amphotericin B. Several non-C. gattii/neoformans species complex (clades III to V) had MICs equal to or above the ECVs established for C. deuterogattii and C. neoformans for all the three antifungal drugs tested. Finally, all the non-C. gattii/neoformans clinical isolates (clades III to V) produced more melanin than the environmental isolates might reflect their particularly enhanced need for melanin during in vivo protection. It is very clear that C. gattii/neoformans species complex (clades I and II) strains, in general, show more similar virulence phenotypes between each other when compared to non-C. gattii/neoformans species complex (clades III to V) isolates. These observations together with the fact that P. laurentii and Naganishia spp. (clades III to V) strains were collected from the outside of a University Hospital, identify features of these yeasts important for environmental and patient colonization and furthermore, define mechanisms for infections with these uncommon pathogens.